2017
DOI: 10.1039/c6ta07876a
|View full text |Cite
|
Sign up to set email alerts
|

Successive surface engineering of TiO2 compact layers via dual modification of fullerene derivatives affording hysteresis-suppressed high-performance perovskite solar cells

Abstract: A new successive surface engineering method via a dual modification of TiO2 compact layer by PC61BM and C60-ETA was developed, affording dramatic efficiency enhancement with suppressed-hysteresis current–voltage response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 62 publications
3
68
0
Order By: Relevance
“…After TiCl 4 or PC 61 BM modification of the ETL, the PL intensity substantially decreased. Precisely, the most effective PL quenching is reached by a TiCl 4 treatment with TiCl 4 concentration of 100 × 10 −3 m combined with PC 61 BM modification; the results are well in line with the data discussed above and further prove that TiO 2 NRs modified by a combined TiCl 4 and PC 61 BM treatment can lead to a most efficient extraction of photo‐excited electrons from the light absorber …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…After TiCl 4 or PC 61 BM modification of the ETL, the PL intensity substantially decreased. Precisely, the most effective PL quenching is reached by a TiCl 4 treatment with TiCl 4 concentration of 100 × 10 −3 m combined with PC 61 BM modification; the results are well in line with the data discussed above and further prove that TiO 2 NRs modified by a combined TiCl 4 and PC 61 BM treatment can lead to a most efficient extraction of photo‐excited electrons from the light absorber …”
Section: Resultssupporting
confidence: 87%
“…The influence of the interface engineering on the open‐circuit voltage is evident: for pristine NR, there is a considerable difference between the V OC measured in forward and reverse scans, while after the dual surface modification the difference becomes negligible. Previous work demonstrated that trap states at the TiO 2 ETL surface (i.e., at the ETL/perovskite interface) are the major cause for hysteresis . Our results suggest that the dual ETL modification leads to an effective passivation of such trap states, thereby improving the charge mobility across the ETL/perovskite interface.…”
Section: Resultsmentioning
confidence: 53%
“…To further push this field to commercial applications, the long‐term stability issues should be solved. Apart from the perovskite material itself, the interface contact has been considered as the major cause for this stability issue . Therefore, to address this issue, various interfacial materials have been developed recently .…”
Section: Introductionmentioning
confidence: 99%
“…The amounto f extracted photo-carriers and eventual PCEs tend to be hampered by losses through Shockley-Read-Hall (SRH) recombina-tion. In this regard, there have been many strategies to control the trap level in perovskite thin films through optimizing the grain size, grain boundaries,a nd relateds tructural properties by additive engineering, [7][8][9][10][11][12][13] surface treatments, [14][15][16][17][18][19][20] film casting procedures, [21] etc. To fully reach the potentials of well-engineering perovskite crystallization with reduced bulk traps, there is an urgent need to attain efficient surfacep assivation for perovskite films with which chargee xcitation in the solar cells is promoted with mitigated interfacial charget rapping and resultant SRH recombination.…”
Section: Introductionmentioning
confidence: 99%